Characterization of macroscopic erosion of castellated and flat tungsten surfaces under ITER-like transient plasma loads - Myroshnyk, M.O.; Herashchenko, S.S.; Makhlai, V.A.; Garkusha, I.E.; Aksenov, N.N.; Byrka, O.V.; Chebotarev, V.V.; Kulik, N.V.; Lebedev, S.I.; Shevchuk, P.B.; Staltsov, V.V. (Вопросы атомной науки и техники, 2019)
The damages of tungsten targets with different geometries under repetitive transient hydrogen plasma loads have been studied with a quasi-stationary plasma accelerator QSPA Kh-50. The results of the experiments on target with geometry close to ITER divertor reference design have been compared to results of previous experiments on flat target. The plasma stream parameters were relevant to ITER ELMs (surface heat load above the melting (0.6 MJ/m²) and below the evaporation (1.1 MJ/m²) thresholds of tungsten and pulse duration of 0.25 ms). Surface erosion and dynamics of erosion products have been investigated in the course of repetitive plasma pulses. The crack networks and progressive corrugation occurred on the surface of all the targets exposed to a large number of plasma pulses. Melt motion leads to grow of protuberances on edges of castellated target units. Unlike the flat targets, the separation of liquid/solid particles from the edges of the units is the most significant source of the castellated targets erosion.